A case study of two experienced science teachers' use of practical - Sitole, Kabelo Solly (My University, 2016)
This research project was a case study that investigated how two experienced science teachers, who were undertaking self-studies to improve the use of practical work in their classrooms as part of their BSc Hons research projects, actually developed their strategies for effective use of practical work. This study explored the effectiveness of practical work by analysing 6 ‘typical’ science lessons i.e. introduction, practical session and consolidation lessons in two schools around Gauteng in South African. The research design took a form of classroom observations through audio and video recordings and also interview and questionnaires schedules with the two participant teachers. Abraham and Millar (2008) argued that many science teachers do not implement practical work effectively when teaching in their classrooms and most learners fail to relate what they do in practical work to other aspects of their learning. This research project hoped to find an answer to main research question: How effective are the two participating teachers’ strategies of using practical work to promote conceptual and procedural understanding? The data analysis used a model of effectiveness on the work done by Millar, Marechal and Tiberghien (1999) and Tiberghien (2000). The two teachers focus in these observed lessons was to promote and develop conceptual and procedural understanding. This study found that practical work in some cases was effective in getting the learners to do what was intended for them to do with objects and materials e.g. apparatus, but the was less evidence of the effectiveness of practical work in getting the learners to use the intended scientific ideas from the data they collected and also little evidence of them showing the understanding of what they were intended to understand e.g. cognitive challenge of linking the observables to ideas. The study revealed that learners get more procedural understanding and less conceptual understanding in a given practical activity. The study also revealed that teachers faced a lot of challenges when implementing the use of practical work in their classroom e.g. time constraints, minimum availability of resource, less CAPS training etc. and these challenges often hinders the use of practical work as part of the learning and teaching of science. This study further recommended that the department of education do more to support the teachers in their implementations of certain teaching strategies e.g. practical work and that the use of practical work be considered at the fore-front of learning and teaching of science.
A Research Project submitted to the Faculty of Science, University of the Witwatersrand, Johannesburg, in partial fulfilment of the requirements for the degree of MSc (Sci. Ed). March 2016
Keywords: Science teachers; Science teachers--Study and teaching--South Africa--Johannesburg; Science--Experiments